A family of Mn(ii) complexes exhibiting strong photo- and triboluminescence as well as polymorphic luminescence. Issue 15 (12th July 2021) - Artem'ev, Alexander V.; Davydova, Maria P.; Rakhmanova, Mariana I.; Bagryanskaya, Irina Yu.; Pishchur, Denis P.
Abstract : New Mn(ii ) complexes supported by diphosphine dioxides exhibit strong room-temperature phosphorescence as well as bright triboluminescence and polymorphic luminescence. Abstract : A family of robust metal complexes of [Mn(L)X2 ] and (LH)2 [MnX4 ] type (X = Cl, Br, I) have been synthesized based on xanthene-derived bisphosphine dioxides (L = XantphosO2 or t -Bu-XantphosO2 ). At ambient temperature, the designed compounds exhibit strong green to yellow phosphorescence with quantum yields as high as 90%. Remarkably, complex [Mn(XantphosO2 )Br2 ] reveals polymorphic luminescence, which is a rare phenomenon for Mn compounds. Two polymorphs of this compound, crystallizing in P 1̄ and P 21 / n space groups, display green and yellow luminescence, respectively, with the emission quantum yield being 33 and 50%. Moreover, the "yellow" polymorph features bright triboluminescence upon grinding its crystals. An in-depth photophysical study evidences that the observed phosphorescence is due to the ligand-sensitized 4 T1 → 6 A1 transitions in Mn 2+ ions.